How to improve soil anti-adhesion by studying the micro relief of the cutible surface of digging beetles: Using rotated image with maximum average power spectrum technique to find the predominant directions of the topographic patten. - Setten, Lorena; Guillen, Noelia Belén; Favret, Eduardo Alfredo (Oxford University Press, 2025)
In recent years, our research has focused on the microtopography of different soil-digging beetles, with the aim of identifying the pattern responsible for reducing the adhesion of soil particles to agricultural machinery components [1, 2]. The main characteristic of the microtopography (micro relief) of the cuticular surface of the pronotum of these beetles is the presence of dimples apparently randomly distributed.